Invasive Candidiasis Associated with Adenovirus Pneumonia - Guwani Liyanage; Madhusha Gonapaladeniya; Thushari Dissanayake (Case Reports in Pediatrics)
Invasive Candida infections in immunocompetent children lead to high morbidity and mortality despite available treatment. Candida albicans and Candida parapsilosis are the most common pathogens; however, there are newly emerging pathogenic non-albicans species. Adenovirus accounts for at least 5–10% of respiratory infections in children, and specific serotypes are associated with severe pneumonia. To the best of our knowledge, invasive Candida infection complicating adenovirus-associated pneumonia in immunocompetent children has not been reported previously. Herein, we describe a preschool child with invasive candidiasis associated with adenovirus pneumonia.